Impact of Hurricane Irene on Vibrio vulnificus and Vibrio parahaemolyticus concentrations in surface water, sediment, and cultured oysters in the Chesapeake Bay, MD, USA - Shaw, Kristi S.; Jacobs, John M.; Crump, Byron C. (Frontiers in Microbiology, 2014)
To determine if a storm event (i.e., high winds, large volumes of precipitation) could alter concentrations of Vibrio vulnificus and Vibrio parahaemolyticus in aquacultured oysters (Crassostrea virginica) and associated surface water and sediment, this study followed a sampling timeline before and after Hurricane Irene impacted the Chesapeake Bay estuary in late August 2011. Aquacultured oysters were sampled from two levels in the water column: surface 0.3 m and near-bottom just above the sediment. Concentrations of each Vibrio spp. and associated virulence genes were measured in oysters with a combination of real-time PCR and most probable number enrichment methods, and in sediment and surface water with real-time PCR. While concentration shifts of each Vibrio species were apparent post-storm, statistical tests indicated no significant change in concentration change for either Vibrio species by location (surface or near bottom oysters) or date sampled (oyster tissue, surface water and sediment concentrations). V. vulnificus in oyster tissue was correlated with total suspended solids (r=0.41, p=0.04), and V. vulnificus in sediment was correlated with secchi depth (r=-0.93, p< 0.01), salinity (r=-0.46, p=0.02), tidal height (r=-0.45, p=0.03), and surface water V. vulnificus (r=0.98, p< 0.01). V. parahaemolyticus in oyster tissue did not correlate with environmental measurements, but V. parahaemolyticus in sediment and surface water correlated with several measurements including secchi depth (r=-0.48, p=0.02[sediment]; r=-0.97 p< 0.01[surface water]) and tidal height (r=-0.96. p< 0.01[sediment], r=-0.59,p< 0.01 [surface water]). The concentrations of Vibrio spp. were higher in oysters relative to other studies (average V. vulnificus 4x105 MPN g-1, V. parahaemolyticus 1x105 MPN g-1), and virulence-associated genes were detected in most oyster samples. This study provides a first estimate of storm-related Vibrio density changes in oyster tissues, sediment and surface w